Effect Of Water-Fly Ash-Cement Grouting On The Clayey Subgrade Soil Characteristics of The Tuban-Babat Lamongan-Gresik National Road - Langit, Mohammad Jagad Sekar; Satrya, Trihanyndio Rendy; Soemitro, Ria Asih Aryani; Ferdian, Vidi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The Tuban-Babat-Lamongan-Gresik road section is one of the northern coast sections of Java, Indonesia that experienced road damage that have a low CBR value of around 1.7%-2.9%. In this study, the soil improvement method used is Water Fly Ash Cement Grouting which will be tested on a laboratory scale. Variations in addition to the quantity of grouting material are 3%, 5%, and 7% of dry weight in the test sample, water binder ratio (w/b) variations of 1, 1.5 and 2 with 3 binder composition variations, namely 90% Cement + 10% Fly Ash, 80% Cement + 20% Fly Ash, and 70% Cement + 30% Fly Ash. The selection of the use of Fly Ash in addition to utilizing waste from coal burning activities, relatively cheap prices and effectiveness which has been proven in previous studies.The results show that Water Fly Ash Cement Grouting can affect properties of the sample. The plasticity index which was originally 45.09% to 25.08% and the CBR value which was originally 0.14% to 1.92% at the quantity of grouting material 7% of the dry weight of the test sample, Water Binder ratio (w/b) 1 with a binder composition of 90% Cement + 10% Fly Ash.